A Review of Inertial Navigation Technologies for Remotely Operated Vehicles - LAI Yu; ZHU Jun (Kongzhi Yu Xinxi Jishu)
The inertial navigation system (INS) provides vital location and heading information for remotely operated vehicles (ROVs), which is crucial for ROV navigation and control. The ROV's inertial navigation system mainly relies on pure inertial navigation, leveraging sensors such as gyroscopes and accelerometers to obtain information about the robot's attitude angle and acceleration. The position information is then determined through integral computation. However, due to the accumulative error over time induced by integral computation, pure inertial navigation systems often deploy various ranging or acoustic positioning approaches to yield accurate position information. Diverse combination navigation methods including acoustics, optics, and vision-inertial among others have been employed to date. The focus of future developments in the inertial navigation technology for ROVs is an area of considerable interest and research. From the perspectives of combination methodologies and algorithms, this paper scrutinizes the prevailing tactics for combining and correcting underwater inertial navigation. It highlights the ongoing trend towards developing high-precision, multi-source integrated, and intelligent ROV inertial navigation systems, and enumerates challenges such as addressing low-precision and robustness issues in the application of ROV INS in the industrial domain.